Predictors of financially distressed small and medium-sized enterprises: A case of Malaysia - Abdullah, Nur Adiana Hiau; Zainudin, Nasruddin; Ahmad, Abd Halim @ Hamilton; Md Rus, Rohani (2014)
This study aims to investigate factors contributing to financial distress among manufacturing SMEs.By employing the logistic regression, we find that age, size, debt ratio, sales to total assets and net income to share capital could predict financially distressed SMEs for the 4-year prior to distress model.However, 3-year prior to distress, more variables, namely age, size, debt ratio, short-term to total liabilities, current ratio and EBIT to total assets, are found to be significant.As companies are nearer to distress situation, less number but important variables emerged.Two year prior to distress, age, debt ratio and EBIT to total assets remained significant while one year prior to distress, only debt ratio could predict financially distressed companies.This ratio is found to be consistently significant in all periods.